Class II HLA Epitope Matching—A Strategy to Minimize De Novo Donor‐Specific Antibody Development and Improve Outcomes. Issue 12 (25th October 2013) - Wiebe, C.; Pochinco, D.; Blydt‐Hansen, T. D.; Ho, J.; Birk, P. E.; Karpinski, M.; Goldberg, A.; Storsley, L. J.; Gibson, I. W.; Rush, D. N.; Nickerson, P. W.
Abstract De novo donor‐specific antibody (dnDSA) develops in 15–25% of renal transplant recipients within 5 years of transplantation and is associated with 40% lower graft survival at 10 years. HLA epitope matching is a novel strategy that may minimize dnDSA development. HLAMatchmaker software was used to characterize epitope mismatches at 395 potential HLA‐DR/DQ/DP conformational epitopes for 286 donor–recipient pairs. Epitope specificities were assigned using single antigen HLA bead analysis and correlated with known monoclonal alloantibody epitope targets. Locus‐specific epitope mismatches were more numerous in patients who developed HLA‐DR dnDSA alone (21.4 vs. 13.2, p < 0.02) or HLA‐DQ dnDSA alone (27.5 vs. 17.3, p < 0.001). An optimal threshold for epitope mismatches (10 for HLA‐DR, 17 for HLA‐DQ) was defined that was associated with minimal development of Class II dnDSA. Applying these thresholds, zero and 2.7% of patients developed dnDSA against HLA‐DR and HLA‐DQ, respectively, after a median of 6.9 years. Epitope specificity analysis revealed that 3 HLA‐DR and 3 HLA‐DQ epitopes were independent multivariate predictors of Class II dnDSA. HLA‐DR and DQ epitope matching outperforms traditional low‐resolution antigen‐based matching and has the potential to minimize the risk of de novo Class II DSA development, thereby improving long‐term graft outcome.